Effect of bacterial inoculants on the preservation of alfalfa and whole-plant corn silages - K.K. Bolsen; R.N. Sonon; B.S. Dalke (Kansas Agricultural Experiment Station Research Reports, 1993)
Inoculated and control alfalfa and corn silages were compared in pilot-scale silos. Inoculated silages for both crops had higher lactic acid contents and DM recoveries and lower values for pH, acetic acid, ethanol, and ammonia-nitrogen than controls"”evidence that the inoculants produced a more efficient fermentation. These results are consistent with numerous studies that compared untreated and inoculant-treated silages over a wide range of crops and ensiling conditions in our research during the past several years.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Silage; Inoculant; Preservation; Alfalfa; Corn